Group Dynamics in Play and Games among Pre-school Children - Lucia Malinova; Bozhidar Angelov (Ignatianum University Press, 2019)
The article covers topical problems related to the group dynamics theory and practice in play and games in nurseries. It offers a brief overview of various research findings in the pedagogy, social psychology, cultural theories and mass media. According to the authors, play activities and games recreate social interactions of people. These activities broaden children's views and enhance interaction skills. They should be regarded as part of children's upbringing and education. Activities based on play and games in pre-schools are related to other factors which develop and foster children's social skills. The findings of the present study verify that group dynamics in play and games among children mirrors children's social behaviour and helps children build up and enhance their interaction skills.